Atributos químicos do solo e da planta de Tectona grandis em diferentes idades - Gava, Fernando Henrique (2023)
Due to the importance of soil nutrients, it is necessary to understand their use, demand and compartmentalization in plants. Teak is a species of high economic value and it is planted by several countries around the world, with emphasis on Brazil, whose area has increased more and more during years. In order to better understand the dynamics of nutrients in soil and teak trees over the years, this work was developed in three chapters, the first was to contextualize the nutrients in teak and its characteristics; the second aimed to correlate the chemical properties of soil, leaf, bark and teak trunk at four different ages with the native forest; and the third aimed to measure the stock of nutrients in teak and diagnose which nutrients correlate more with the accumulation of biomass in the wood for teak clonal and seminal material. These studies were carried out in stands of clonal and seminal teak aged between 5 and 20 years, with the following collection sites being established 5-year-old clonal teak (TC5), 10-year-old clonal teak (TC10), 10-year-old seminal teak (T10), 15-yearold seminal teak (T15), 20-year-old seminal teak (T20) and an area with native forest (MN). In each study area, trenches were opened at depths of 0-10, 10-20, 20-40, 40- 60 and 60-100 cm and deformed and undisturbed soil samples were collected. The closest four trees of each trench were felled, cubed and collected leaf and disc samples from each individual tree. With the data (soil, leaf, bark and wood) nutritional analyzes were carried out. To compare the results, analysis of variance (Scott-Knott test) was performed for soil nutrients in teak and MN stands, for organic matter and total organic carbon stocks and nutrients from leaves, bark and teak wood. Principal component analysis of teak trees with soil fertility up to 20 cm depth was performed. After the analyzes, the soil pH in the teak areas increased (from 3.62 to 5.53) due to the increase in CEC and base saturation, resulting in a reduction in aluminum saturation. The total organic carbon stock at 100 cm depth was the same for MN and seminal teak from 10 years of age (average of 31.18 Mg ha-1). For the leaf compartment the nutrients N, Ca, Mg, P, K, Cu and B were concentrated in greater amounts for clonal theca at 5 years of age. Fe increases with teak age and is one of the most important nutrients with high and positive correlations with biomass. P and Fe increasing with age for both clonal and seminal material. Thus, it was concluded that soil pH in teak plantations up to 20 years does not decrease; that teak influences the dynamics of soil nutrients; the hierarchy of importance of the nutrients with the biomass for the clonal material was Fef > Cac > Fem > Pm > Mnc > Mnf and for the seminal material Pm > Cac > Pf > K > Fem > Mn > Kf > Bc > Kc > Caf > Fec > Fef, with Fe, P and Ca being the most important nutrients for teak.